2021
DOI: 10.3390/nano11020462
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dots as a Good Carriers of Unsymmetrical Bisacridines for Modulating Cellular Uptake and the Biological Response in Lung and Colon Cancer Cells

Abstract: Nanotechnology-based drug delivery provides a promising area for improving the efficacy of cancer treatments. Therefore, we investigate the potential of using quantum dots (QDs) as drug carriers for antitumor unsymmetrical bisacridine derivatives (UAs) to cancer cells. We examine the influence of QD–UA hybrids on the cellular uptake, internalization (Confocal Laser Scanning Microscope), and the biological response (flow cytometry and light microscopy) in lung H460 and colon HCT116 cancer cells. We show the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Additionally, UAs turned out to be very potent in inhibiting the growth of HCT116- and H460-derived spheroids [ 27 ]. Moreover, some of the UAs were conjugated with quantum dots (QDs), which improved their delivery to cancer cells [ 28 , 29 , 30 ]. In the presented study, we wanted to show the cellular mechanism of action of four UA derivatives in relation to changes in c-Myc and K-Ras proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, UAs turned out to be very potent in inhibiting the growth of HCT116- and H460-derived spheroids [ 27 ]. Moreover, some of the UAs were conjugated with quantum dots (QDs), which improved their delivery to cancer cells [ 28 , 29 , 30 ]. In the presented study, we wanted to show the cellular mechanism of action of four UA derivatives in relation to changes in c-Myc and K-Ras proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we studied the influence of navigating molecules (folic acid) and incubation time (1, 24, 48, and 72 h). Based on our previous experience with cellular uptake studies [27], we selected for further experiments nanoconjugates with QD green . The amount of the delivered C-2028 compound to cancer cells was higher in the case of the use of QD green as a drug delivery platform compared to QD red .…”
Section: Cellular Uptakementioning
confidence: 99%
“…We showed that the efficient procedure for the synthesis of QD−UA hybrids successfully increases the cytotoxic activity of UAs in cancer H460 cells and has protective effects on normal MRC-5 and CCD 841 CoN cells [25]. We investigated also the influence of conjugation of UAs with QDs on the cellular uptake and the biological response in lung H460 and colon HCT116 cancer cells as well as normal MRC-5 and CCD 841 CoN cells [25,27].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the biological effects of these compounds demonstrated their ability to suppress 3D cancer spheroid growth [4]. Moreover, their anticancer activity was enhanced when bound to quaternary quantum dots, resulting in selective upregulation of their cellular uptake [5][6][7]. Our previous studies demonstrated that UAs undergo metabolic transformations which retain the compounds' dimeric structure.…”
Section: Introductionmentioning
confidence: 99%